2023
DOI: 10.26434/chemrxiv-2023-5w45b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Geometry and Electronic Structure of Copper Corroles

Abstract: Copper corroles are known for their unique multiconfigurational electronic structures in the ground state, which arise from the transfer of electrons from the π orbitals of the corrole to the d orbital of copper. While density functional theory (DFT) provides reasonably good molecular geometries, the determination of the ground spin state and the associated energetics is heavily influenced by functional choice, particularly the percentage of Hartree-Fock exchange. Using extended multireference perturbation the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…The current study is inspired, in part, by this statement. 102 In 2015, fully internally contracted (FIC)-CASPT2 analytical gradients, 73 followed soon after by their multistate extensions, 71 made such optimizations feasible. In the scan along the Ω angle using state-specific (SS)-CASPT2 and MS-CASPT2, Pierloot et al found a state crossing for the bare and 5,10,15triphenyl copper corroles, but saw no such crossing in the MS-CASPT2 surface, attributing this to known failures in the multistate approach.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The current study is inspired, in part, by this statement. 102 In 2015, fully internally contracted (FIC)-CASPT2 analytical gradients, 73 followed soon after by their multistate extensions, 71 made such optimizations feasible. In the scan along the Ω angle using state-specific (SS)-CASPT2 and MS-CASPT2, Pierloot et al found a state crossing for the bare and 5,10,15triphenyl copper corroles, but saw no such crossing in the MS-CASPT2 surface, attributing this to known failures in the multistate approach.…”
Section: ■ Results and Discussionmentioning
confidence: 99%